The effects of remuneration and reward systems on employee motivation in Luxembourg - Lisa Schreiner (European Institute for Knowledge & Value Management (EIKV), 2018)
The following thesis has the objective to determine employee's motivation based on the providing of remunerations and rewards. In order to achieve the objective of the thesis, theoretical information is provided on the subjects of remuneration and reward. Furthermore, there will be a literature review of motives and motivation. Another objective is to give every reader a clear overview of the common rewards in Luxembourg and provides an insight into the issue of motivation. Through this information, this thesis can help to better understand its own motivation and probably to adapt behaviors. This thesis includes a survey of a selection of remuneration and rewards that links the topic of remuneration and reward to the motivation that may occur. Moreover, humans only know their own opinion of rewards and motivation. The results of the survey are therefore interesting because they show how other employees are motivated and their views on the provided rewards. The thesis and the linked survey may be viewed as an example that helps companies in developing a questionnaire or interviews in order to introduce the right rewards.
Keywords: 330